Dynamic Coefficient Investigation for Supercritical Carbon Dioxide Dry Gas Seal Based on Complete Variable Perturbation Model - Ruqi Yan; Baodui Chai; Lu Ma; Hanqing Chen; Xuexing Ding (Lubricants)
In this work, a new model to analyse the dynamic characteristic coefficient of the S-CO2 dry gas seal was reported. Taking into account that the flow within the S-CO2 dry gas seal is close to adiabatic flow, the impact of the temperature change on the dynamic characteristic coefficient of the gas film cannot be ignored. To address this issue, a complete variable perturbation model (CVPM) under the adiabatic flow process was established using the frequency perturbation method while considering multiple complex effects. Then, the finite difference method was used to solve the CVPM. The gas film’s dynamic stiffness and damping coefficients were calculated and analysed for different conditions, operating parameters, and frequency ratios. From our analysis, it was demonstrated that the dynamic coefficient of the gas film exhibited frequency dependence. The turbulence coefficient perturbation had the most remarkable influence on the gas film’s dynamic coefficient, compared to the temperature, viscosity, and centrifugal inertia force perturbations. The isothermal flow, adiabatic flow, inlet pressure, and inlet temperature also affected the magnitude of the dynamic characteristic coefficient of the gas film. However, no significant impact on their tendency to vary with the frequency ratio was found. Our work provides new theoretical support for the dynamic analysis of S-CO2 dry gas seals, which is of great importance for future applications.